IMPLEMENTASI METODE MULTIFACTOR EVALUATION PROCESS(MFEP) DALAM SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMA SUBSIDI KEPEMILIKAN RUMAH PADA PT JAYA ALAM PROPERTY - Pratama Huda , Bagas; Heru Mujianto , Ahmad (Inovate, 2023)
The importance of determining the eligibility of recipients of subsidized housing at PT Jaya Alam Property is a stage that must be carried out, where there must be several criteria that must be achieved in order to pass this stage, namely from these criteria. The purpose of this research is to create a system that can help PT Jaya Alam Property in identifying beneficiaries of Subsidized housing, a government program, is an alternative for those with low incomes so that their basic necessities, including housing, may be addressed with ease, especially for those who are already married.. So that the Multi Factor Evaluation Process (MFEP) method will really help determine the eligibility of subsidized housing recipients in a very subjective, intuitive, efficient and effective way. The MFEP method's phases include to determine the importance of each need, fill in the loyalty value, calculate the evaluation weight, then add the evaluation value is calculated by adding all the evaluation weights. to determine the eligibility criteria for subsidized housing recipients. Keywords: SPK, Method, Recipients of Subsidies, PT Jaya Alam Property, MFEP